Cross-Sectional Estimates of Cost Economies in Stock Property-Liability Companies - Allen, Robert F. (The Review of Economics and Statistics, 1974)
The insurance industry is populated by some 2867 insurance companies each of which is the object of numerous rules promulgated and enforced by the various State Insurance Commissions.1 Some of the more important rules have to do with new company formations and mergers between existing insurers. If, as seems reasonable, the administration of these rules rests in part on the Commissioner's perceptions concerning the nature and extent of cost economies underlying insurer operations, the recent papers by Hammond, Melander and Shilling (H-M-S) (1971) and Houston and Simon (1970) provide an interesting contrast and deserve more than the usual notation in the files of those concerned with the forces shaping the structure of financial and nonfinancial markets in the American economy. An important concern of these studies has been the identification of insurer size beyond which substantial cost savings cease to accompany increases in insurance output.2 In this regard, the H-M-S study suggests that significant cost savings are realizedby stock property-liability companies up to a size of $300 to $600 million as measured by annual net premium writings.3 This contrasts sharply with the H-S study which finds significant cost savings cease to accrue to life insurers once annual premiums exceed $100 million.4 As there is nothing in the formal organization of life companies vis-a-vis property-liability companies that can account for these differing estimates, and as there is little logic to support the belief that substantial cost savings are dependent on the size of property-liability insurers,5 further research into the behavior of property-liability costs seems appropriate. Accordingly, this paper provides new estimates of the extent of cost economies in the property-liability industry based on a new sample and regression model. The rationale underlying the regression model is set forward in the first section of the paper; the regression results in the second section; and the third section of the paper concludes with summary observations on the results.